Distinguishing Majorana bound states and Andreev bound states with microwave spectra. (13th March 2018) - Zhang, Zhen-Tao
Abstract: Majorana fermions are a fascinating and not yet confirmed quasiparticles in condensed matter physics. Here we propose using microwave spectra to distinguish Majorana bound states (MBSs) from topological trivial Andreev bound states. By numerically calculating the transmission and Zeeman field dependence of the many-body excitation spectrum of a 1D Josephson junction, we find that the two kinds of bound states have distinct responses to variations in the related parameters. Furthermore, the singular behaviors of the MBSs spectrum could be attributed to the robust fractional Josephson coupling and nonlocality of MBSs. Our results provide a feasible method to verify the existence of MBSs and could accelerate its application to topological quantum computation.